Healthy buildings and materials - Doucette, Martin; Beach, Frank; Wann, David; American Institute of Architects; ICBO Video Productions ([S.l.] : American Institute of Architects : ICBO Video Productions ; New York : Distributed by Insight Media, 1993)
A special series featuring panel discussions among architects, engineers, planners, and developers that examine multidisciplinary approaches to projects and holistic, life-cycle design on environmentally responsible architecture
Title from title screen
Camera, Connie Day, Norman Henderson, Doug Koztoski ; editor, Lorita Doucette
Moderator, Denis Hayes
DVD format
Keywords: Architecture -- Environmental aspects; Architecture and energy conservation; Indoor air pollution; Building materials -- Environmental aspects; Architecture and climate; Buildings -- Environmental engineering